CROHN'S DISEASE AMONG CHILDREN AND TEENAGERS: DIAGNOSTICS AND UP TO DATE THERAPY APPROACHES - S.Yu. Tereshchenko (Union of pediatricians of Russia, 2009)
The article presents modern data on prevalence, risk factors, diagnostics and treatment of Crohn's diseases among children and teenagers. It covers the issues of nutritive support, enteral feeding, demonstrative data on induction and remission support. The article gives complete information about modern therapy approaches to refractory forms of Crohn's diseases based on a new trend of «biological therapy» - more specifically, based on infliximab.Key words: kids, teenagers, Crohn's diseases, diagnosis, treatment.